Inflammation mediates the effect of discrimination, religiosity, and friendship network on expression of the Tp53 cancer suppressor gene. (April 2019) - Simons, Ronald L.; Lei, Man-Kit; Carter, Sierra; Beach, Steven R.H.; Gibbons, Frederick X.; Gerrard, Meg; Philibert, Robert A.
Abstract: Objective: Chronic inflammation and expression of the TP53 gene are two biomarkers that have been identified as particularly important in the etiology and progression of cancer. While much is known about the determinants of inflammation, there is currently little information regarding the causes of variation in the functioning of TP53, even though it has been recognized for 40 years as the most potent of the cancer suppressor genes. The current paper explores the interrelationship between these two biomarkers and investigates the extent to which they are influenced by the social environment. Methods: Using structural equation modeling (SEM) and longitudinal observational data from a sample of several hundred African Americans, we tested the hypothesis that adversity – operationalized as racial discrimination- and coping resources – operationalized as religiosity and black friends - influence expression of TP53, for better or worse, through their impact on inflammation. Results: Correlational analysis showed inflammation and TP53 to be inversely related. Further, discrimination was positively related to inflammation and negatively related to TP53 expression, whereas religiosity and black friends were both negatively related to inflammation and positively related to TP53 expression. Finally, SEM indicated that the effect of the social environmental variables on TP53 expression was indirect through level of inflammation. Conclusions: In addition to its established contribution to cancer through DNA damage and cell proliferation, inflammation likely increases cancer risk indirectly by inhibiting expression of the TP53 cancer suppressor gene. Hence environmental and stress management interventions may do more than reduce inflammation's cell damaging effects; they may also lessen the chances of cancer by increasing expression of TP53 . Highlights: Discrimination, religiosity, and black friends showed significant associations with inflammation and TP53. The effect of discrimination, religiosity, and black friends on TP53 was indirect through level of inflammation. Inflammation likely increases cancer risk indirectly by suppressing the TP53 cancer suppressor gene. Environmental and stress management interventions may lessen the chances of cancer by increasing expression of TP53.